Structural Complexity in Coral Reefs: Examination of a Novel Evaluation Tool on Different Spatial Scales - Yanovski, Roy; Nelson, Peter A.; Abelson, Avigdor (Frontiers in Ecology and Evolution, 2017)
1. Structural complexity is a key factor in ecology, often positively linked to biodiversity and carrying capacity of habitats. However, defining quantitatively the ecological role of structural complexity remains a challenge, mainly due to its unclear definition and lack of accurate measurement tools and indices. The most common structural complexity indices used in ecological studies are the "Rugosity index" and "Fractal Dimension". However, these indices cannot appraise, or overlook certain complexity indications that may play important ecological roles, such as the different characteristics of structural elements or different spatial scales of structural complexity. 2. This study attempts to tackle these challenges by: 1. examining a new method for structural complexity measurement ("Point-Intercept Contour" or PIC), which may allow calculation of different complexity indices; 2. measuring structural complexity on different spatial scales, each of which may affect or reflect on different ecological factors; and 3. comparing three different indices of structural complexity (i.e., "Rugosity index", "Coefficient of Variation" and "Neighbor's Distance") at different spatial scales, in natural reefs in the Philippines. 3. The PIC method has proven to be easy to perform, provides informative data about structural complexity elements, and enables the calculation of all three indices on different spatial scales. 4. The different spatial scales revealed different patterns among sites that emphasize the importance of considering spatial scaling when expressing different ecological aspects that may indicate reef health. 5. The three indices showed similar general trends, with some differences between scales that reveal some advantages and some drawbacks to each index. 6. The study demonstrates the importance of structural complexity at different spatial scales, and suggests a series of considerations for the use of relevant methods and indices with emphasis on an inexpensive, facile tool for quantitative structural complexity measurements.